Pertanggungjawaban Pidana Deepfake Porn Berbasis AI: Studi Perbandingan dan Implikasi Global - Nurulhuda Irawati (Jurnal Hukum Lex Generalis, 2026)
This study examines the criminal liability of AI-based deepfake porn perpetrators. The background is the rise of sexual digital manipulation, while Indonesian regulations still focus on general pornography. With the formulation of the problem obtained how the legal arrangements and policy recommendations, as well as methods of using normative juridical approach with a comparative study of Australia and South Korea. The discussion places national responses within the framework of international human rights (ICCPR Article 17), cyber cooperation instruments (Budapest Convention), and global AI regulations. Recommendations: criminalization of production, dissemination, possession, takedown mechanisms, preservation of evidence, as well as cross-border MLA cooperation.